2019
DOI: 10.1371/journal.pone.0223143
|View full text |Cite
|
Sign up to set email alerts
|

Modeling spatial variation in density of golden eagle nest sites in the western United States

Abstract: In order to contribute to conservation planning efforts for golden eagles (Aquila chrysaetos) in the western U.S., we developed nest site models using >6,500 nest site locations throughout a >3,483,000 km2 area of the western U.S. We developed models for twelve discrete modeling regions, and estimated relative density of nest sites for each region. Cross-validation showed that, in general, models accurately estimated relative nest site densities within regions and sub-regions. Areas estimated to have the highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(42 citation statements)
references
References 74 publications
(100 reference statements)
3
36
0
Order By: Relevance
“…Thus, quantile binning resulted in the highest bins containing a disproportionately large range of the values, while the lower bins more finely differentiated among the smaller predicted values. Similarly, ,20% of the study area had Golden Eagle nest-site density values .1.0 AAF, yet contained .80% of known Golden Eagle nests (Dunk et al 2019a). Although other binning methods might be reasonable and useful, our method of binning model values using quantiles worked very well, based on our evaluation of independent mortality data, which indicated that even small increases in Golden Eagle density (e.g., bin 5 vs. bin 6; Fig.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…Thus, quantile binning resulted in the highest bins containing a disproportionately large range of the values, while the lower bins more finely differentiated among the smaller predicted values. Similarly, ,20% of the study area had Golden Eagle nest-site density values .1.0 AAF, yet contained .80% of known Golden Eagle nests (Dunk et al 2019a). Although other binning methods might be reasonable and useful, our method of binning model values using quantiles worked very well, based on our evaluation of independent mortality data, which indicated that even small increases in Golden Eagle density (e.g., bin 5 vs. bin 6; Fig.…”
Section: Discussionmentioning
confidence: 75%
“…Given the model's accurate predictions in the PRECorp service area, we believe the model will be immediately useful to land managers, utilities, and conservationists throughout the Northwestern Plains region. Because we previously developed models of Golden Eagle and power pole density for the majority of ecoregions occupied by Golden Eagles in the western USA (Dunk et al 2019a, the analysis presented here is a case study in only one of many regions where such risk analyses are possible.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations